Numerical modelling of storm surge, nutrient pollution and saltwater intrusion in a large estuary with typhoon effects. (September 2022) - Zhang, Hong-xing; Shen, Yong-ming; Zhao, An-dong; Tang, Jun
Abstract: A coupled modelling framework, consisting of the storm surge model and the European Regional Seas Ecosystem Model (ERSEM), has been established to examine hydrodynamics process during Typhoon Hagupit and its role on nutrient and salinity dynamics in the Pearl River Estuary (PRE). The accuracy of modelling framework was reasonably validated against measured typhoon wind, storm tide, and water quality data. Further analysis suggests Hagupit significantly increases water levels in the PRE. Meanwhile, the seaward residual currents apparently and chaotically change. The phosphate and dissolved inorganic nitrogen concentrations decrease by 0.2–1.8 and 20–88.6 μmol/L in the most area from the downstream of narrow river channels to offshore region due to the variations of hydrodynamics, while small difference was detected in upstream narrow channels and open sea. By contrast, salinity distribution showed opposite variation. Statistically, the typhoon winds alleviated the averaged nutrient pollution in the whole PRE, while causing serious saltwater intrusion. Highlights: A coupled storm surge-water quality modelling framework is developed. The accuracy of the coupled model is validated against in-situ measured data. The hydrodynamics, nutrient and salinity dynamics during a typhoon are presented. The study improves the understand of water environment evolutions during typhoons.